Review of the treatment of the orthographic rules of the spelling g and j in the manuals of second and third cycle of Primary Education and its impact on teaching - Serafín Ayala Ato; Andrés Montaner Bueno (Universidad de La Rioja, 2017)
The objective of this study is to analyze the level of spelling competence regarding the use of the spelling g and j which the students of sixth year of primary education have. To do this, we use a sample composed of 120 students to which we apply a questionnaire of theoretical and practical nature to determine the domain that they have about the rules of use that regulate these contents. The results of this show us that the degree of acquisition of these rules is quite poor, as only 24 students have some concise knowledge of theoretical provisions and only 7 are able to perform the proposed activities successfully. We believe that one of the causes of these poor results is in the didactic perspective with which textbooks deal with the explanation of these precepts. In this respect, we have made a critical research in the way in which the most used textbooks in this educational stage deal with the spelling content about g and j and which are also required by the existing school curricula (LOE and LOMCE).